The emerging double-edged sword role of Sirtuins in the gastric inflammation-carcinoma sequence revealed by bulk and single-cell transcriptomes - Wang, Mengyang; Bi, Chenxiao; Li, Hong; Lu, Lizhen; Gao, Tao; Huang, Panpan; Liu, Chengxia; Wang, Bin (Frontiers in Oncology, 2022)
Histone modification and inflammation-carcinoma sequence (ICS) have been acknowledgedly implicated in gastric carcinogenesis. However, the extremum expression of some histone modification genes (HMGs) in IM rather than GC perplexes the roles of HMGs in ICS. In this study, we assumed an explanation that the roles of HMGs in ICS were stage specific. Bulk-RNA-seq on endoscopy biopsy samples from in total of 50 patients, accompanied with reanalysis of a set of published single cell transcriptomes, profiled the transcriptomic features of ICS composited by chronic superficial gastritis (SG), atrophy gastritis (AG), intestinal metaplasia (IM), and early gastric cancer (GC). Differential analysis observed significantly peaked expression of SIRT6 and SIRT7 at IM. Weighted correlation network analysis on bulk transcriptome recognized significant correlations between SIRT1/6 and IM. Single cell atlas identified one subgroup of B cells expressing high level of TFF1 (TFF1hi naive B cell) that theoretically played important roles in defending microbial infection, while SIRT6 displayed positive correlation with TFF1low naive B cell. Moreover, gene set enrichment analysis at different lesions (SG-AG, AG-IM, and IM-GC) highlighted that gene sets contributing to IM, e.g., Brush Border, were largely enriched from co-expressing genes of Sirtuins (SIRTs) in AG-IM. The genes negatively correlated with SIRT6 were surveyed in public databases, and the results considered SIRT6 as tumor suppressors. All above observations were then confirmed by serial section-based immunohistochemistry against Ki-67, MUC2, MUC5AC, p53 and SIRT6 on the endoscopic submucosal dissection tissue. By contrast, the expression of the other HMGs were vagaries even opposite within same family. Taken together, this study preliminary demonstrated the two-edged sword role of SIRTs in ICS, and by extension, that the roles of HMGs in ICS were probably stage specific. Our study may remind new insights and attentions in gastric prevention and therapy targeting HMGs.